DETERMINATION OF VITAMIN C AND MINERAL CONTENT OF TWO LOCAL SPECIES OF Carica papaya (SAMBA AND HORTUS GOLD PAPAYA) AT VARIOUS STAGES OF RIPENING - Aroh, A. O.; Omoniyi, K. I.; Mohammed, F. R. (FUDMA JOURNAL OF SCIENCES, 2023)
Papaya (Carica papaya Linn) is a popular fruit grown in the tropical and subtropical parts of the world, also known as "pawpaw". The fruit is consumed when ripe and also processed. The many benefits of papaya are owed due to the high content of Vitamin A, B and C, and minerals. This study aimed at determining the concentration of vitamin C in two species of the fruits as a function of the ripening periods, using the redox titration method indicated that the concentration of vitamin C decreased from 98 mg/kg to 70 mg/kg in Samba papaya and from 96 mg/kg to 68 mg/kg in the Hortus gold papaya with ripening period. Samba papaya is recommended for vitamin C enhancement at the early ripening stage. Calcium, magnesium and potassium concentrations determined using atomic absorption spectrophotometry decreased in concentration with storage day. Domestic and industry supply of vitamin C and essential minerals is key to health need to be obtained from fruits at the optimum stage.